Evaluation of elemental profiling methods, including laser-induced breakdown spectroscopy (LIBS), for the differentiation of Cannabis plant material grown in different nutrient solutions. (June 2015) - El-Deftar, Moteaa M.; Robertson, James; Foster, Simon; Lennard, Chris
Highlights: Application of LIBS, ICP-MS, LA-ICP-MS and μXRF for the analysis of Cannabis plant. Discrimination of Cannabis is evaluated based on their elemental composition data. It is possible to correctly associate Cannabis with a particular nutrient. ICP-MS, LA-ICP-MS and LIBS are suitable methods for the analysis of Cannabis plant. Abstract: Laser-induced breakdown spectroscopy (LIBS) is an emerging atomic emission based solid sampling technique that has many potential forensic applications. In this study, the analytical performance of LIBS, as well as that of inductively coupled plasma mass spectrometry (ICP-MS), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) and X-ray microfluorescence (μXRF), was evaluated for the ability to conduct elemental analyses on Cannabis plant material, with a specific investigation of the possible links between hydroponic nutrients and elemental profiles from associated plant material. No such study has been previously published in the literature. Good correlation among the four techniques was observed when the concentrations or peak areas of the elements of interest were monitored. For Cannabis samples collected at the same growth time, the elemental profiles could be related to the use of particular commercial nutrients. In addition, the study demonstrated that ICP-MS, LA-ICP-MS and LIBS are suitable techniques for the comparison of Cannabis samples from different sources, with high discriminating powers being achieved. On the other hand, μXRF method was not suitable for the discrimination of Cannabis samples originating from different growth nutrients.